Methane hydrate dissociation using inverted five-spot water flooding method in cubic hydrate simulator - Li, Gang; Li, Xiao-Sen; Li, Bo; Wang, Yi (Energy, 2014)
The combination forms of the hydrate dissociation methods in different well systems are divided into 6 main patterns. Dissociation processes of methane hydrate in porous media using the inverted five-spot water flooding method (Pattern 4) are investigated by the experimental observation and numerical simulation. In situ methane hydrate is synthesized in the Cubic Hydrate Simulator (CHS), a 5.832-L cubic reactor. A center vertical well is used as the hot water injection well, while the four vertical wells at the corner are the gas and water production wells. The gas production begins simultaneously with the hot water injection, while after approximately 20 min of compression, the water begins to be produced. One of the common characteristics of the inverted five-spot water flooding method is that both the gas and water production rates decrease with the reduction of the hydrate dissociation rate. The evaluation of the energy efficiency ratio might indicate the inverted five-spot water flooding as a promising gas producing method from the hydrate reservoir. (C) 2013 Elsevier Ltd. All rights reserved.